On the distribution of Campsicnemus armatus (Zetterstedt, 1849) species group (Diptera: Dolichopodidae) - I.Ya. Grichanov (Acta Biologica Sibirica, 2019)
The Campsicnemus armatus species group differs from the other groups in simple male legs, but with the mid tibia bearing a comb-like posteroventral row of blunt-ended bristles. It includes the Palaearctic Campsicnemus armatus (Zetterstedt, 1849), C. pumilio (Zetterstedt, 1843), C. vtorovi Negrobov et Zlobin, 1978, and C. caffer Curran, 1926, known from northern and southern Africa. C. armatus var. deserti Vaillant, 1953 (unavailable name) from Algeria is associated with C. caffer, which is now spread in the two zoogeographical Regions. New records are given for C. armatus, C. vtorovi and C. caffer. Modified couplets in a key to Palearctic species of Campsicnemus and a new key to Afrotropical species of the genus are provided. Photographs of male antenna and mid tibia of species of the Campsicnemus armatus group are published for the first time.